Unveiling of Equality: 1 Corinthians 11:2-16 - Shoemaker, Thomas R (Biblical theology bulletin, 1987)
Are Paul's writings regarding women helpful for people today who look to Scripture for guidance on issues involving human liberation? Efforts, both traditional and non-traditional, to interpret some key Pauline texts can be well served by the present author's proposal for the proper reading of 1 Cor 11:2-16 on the veiling of women. Supported by the passage's structural emphasis on verse 10 (which he translates "the woman ought to have liberty [exousia] over her head" (based on the identification of a chiastic arrangement in verses 2-16, Shoemaker sees Paul's famous discussion of veiling as including a quote derived from those who would have women submit to veiling and accordingly to a hierarchical structure. To this Paul responds that liberty ought not thus to be taken back from women whose equality properly follows from their discipleship to Christ Jesus.